Spectroscopic, Magnetic and Morphological studies of MgFe2O4 Nanopowder - Naaz, Farhana; Lahiri, Preeti; Kumari, Chanda; Kumar Dubey, Hemant (Physics and Chemistry of Solid State, 2023)
Spinel type nano ferrite compound MgFe2O4 was synthesized through sol gel technique using metal nitrates as precursors. The phase composition, morphology and elemental analysis of magnesium ferrite (MgFe2O4) were performed by X-ray diffraction, fourier transform infrared, atomic force microscopy, energy dispersive x-ray and scanning electron microscopy, analyses. The sample's X-ray diffraction pattern verifies the existence of single phase material, with the size of its crystallites estimated to be 39.9 nm. Fourier transform infrared examination supported metal-oxygen vibrations corresponding to tetrahedral and octahedral sites, respectively. From scanning electron microscopy image, grain size obtained about 97.7 nm. Raman spectra of the sample shows five Raman active modes (A1g + Eg + 3F2g), which is compatible with the spinel structure. Magnetic measurement study at room temperature shows a hysteresis loop behaviour with a low saturation magnetization value, 27.192 emu g-1 and a small coercivity value. The optical band gap determined using UV-visible transmittance spectra. Additionally, X-ray photoelectron spectroscopy are used to confirm oxidation states and explore the chemical composition of the sample.